River mouth morphodynamics and deflection over the short term: effects on spit growth and mangrove dynamics - Oyedotun, Temitope D. Timothy; Nedd, Gordon Ansel (Frontiers in Environmental Science, 2023)
The river mouth shows the influence of the dynamics of sediment deposition and the processes organising the deposits. The river mouths of the Guyana coast, as with other coastal systems in the Guianas, are influenced by the deposition of mud banks from the Amazon River and other rivers. This study analysed and probed the influence of the riverine and marine influences on small river mouth morphological developments. In this study, the morphological dynamics of the system were carried out from satellite images through the comparison of the inter-annual morphodynamics of the river mouths, complemented by data from hydrodynamic processes among others. This study demonstrates that the recent advancement and availability of Synthetic Aperture Radar (SAR), remotely sensed data, allow for the classification of migrating river mouth action and processes; effective monitoring of mudflats development and spit formation; and, the exhibition of river mouth transitioning and infilling. Sentinel-1 images of the Mahaica-Mahaicony river mouth in Guyana were processed and analysed using Google Earth Engine (GEE) and ArcGIS to observe the mud dynamics and its effects on deflecting the river mouth, influencing the development of spit and mangrove dynamics. The results of the analyses show that the dynamics of the mud shoal and river mouth are governed by feedback from various estuarine and hydrodynamic processes resulting from the interactions between the river and ocean. The results have not only highlighted the importance of mud infilling and sediment build-up for spit development and river-mouth deflection but the impact of the sediment morphological dynamics on the ecosystem (mangrove) associated with the river mouth.